MODEL PENDIDIKAN INKLUSI BAGI ANAK USIA DINI DI PAUD TERPADU PUTRA HARAPAN PURWOKERTO - Azhariyanti Mei Ghita; Wahyuningsih Wahyuningsih; Zakiyah Ulfa (IAIN Purwokerto, 2017)
Abstract: Inclusion education is one model of education that mixes students or children with special needs (ABK) with other students (normal) to study together in a classroom. The curriculum used in inclusive education is the same as that used in public schools, only the curriculum for children with special needs (ABK) is more specific and in accordance with the abnormalities that each child suffers. According to the researcher, the learning process in inclusion class with cluster model which implemented in PAUD Terpadu Putra Harapan Purwokerto can be said successful. This can be seen from the development of children with special needs (ABK) is increasing. In addition, it can happen because of various factors that support the process of learning model of inclusion education. Such as: factors of the principal, teachers, parents, and peers. Keywords: Education, Inclusion, Early Childhood Education